Detection and diversity of maize yellow mosaic virus infecting maize in Nigeria - Yahaya, A.; Dangora, D.B.; Alabi, O.J.; Zongoma, A.M.; Kumar, P. Lava (Springer, 2019)
Maize yellow mosaic virus (MaYMV; genus Polerovirus; family Luteoviridae) was recently characterized from maize in China and subsequently detected in mixed infection with sugarcane mosaic virus (genus Potyvirus; family Potyviridae) in sugarcane and itch grass in Nigeria. This study was conducted to understand the status and genetic diversity of MaYMV in maize fields in the northern guinea savannah region of Nigeria. A survey was conducted in 2017 and maize (n = 90) and itch grass (n = 10) plants suspected of virus infection based on appearance of mosaic and/or yellowing symptoms were sampled in Kaduna (n = 65) and Katsina (n = 35) states. The samples were screened individually by reverse transcription polymerase chain reaction using the genus-specific primers targeting poleroviruses and potyviruses Pol-G-F and Pol-G-R primers encompassing the partial P1–P2 fusion protein and coat protein genes of poleroviruses and primer pair CI-For & CI-Rev encompassing the partial cylindrical inclusion proteins of most potyviruses. A subset of amplified DNA fragments was cloned, Sanger-sequenced, and the obtained sequences were bioinformatically analyzed along with corresponding sequences from GenBank. The ~ 1.1 Kb polerovirus fragment was detected in 32.2% (29/90) of the maize samples while all 10 itch grass samples tested negative. BLASTN analysis of sequences derived from six polerovirus samples confirmed the virus identity as MaYMV. In pairwise comparisons, the MaYMV sequences derived in this study shared 97–99% nucleotide identity with sequences of other MaYMV isolates available in the NCBI GenBank. Phylogenetic analysis revealed the segregation of global MaYMV sequences into three host-independent clusters with pattern of geographic structuring.